Sustained censorship in IR (2022-09) (Iran) - Voidly (Voidly Global Censorship Index, 2022)
CRITICAL severity censorship detected in Iran. Data sourced from OONI.
Censorship Incident ID: IR-2022-0005. Severity: critical. Confidence: 75%